DISCONTINUITIES IN RATES OF SEDIMENT ACCUMULATION - Kuz'min V.I.; Nalivkin V.D. (My University, 1989)
Quantization of structure and abrupt discontinuity of natural processes typical in nature. This property has long been known and has been formulated as law of dialectical materialism, which states that quantitative accumulation always leads to abrupt qualitative changes. It has been suggested that the rates of sediment accumulation might also vary in a specific discontinuous fashion. For this purpose, we plotted the depths at which stages and other stratigraphic divisions occur in drillholes versus their absolute ages. The ages of the stratigraphic boundaries were those cited by Afans'yev. We constructed 100 plots for drillholes in various areas of Western Siberia, Mangyshlak, the Pechora Syneclise, the Russian Plate and the Siberian Craton. The considerable number of coincidences among the various plots suggests the important conclusion that, overall, the rates of sedimentation changed simultaneously throughout the globe, although there were some departures from this pattern in some sedimentation basins.